Developing Smart Phone-Based Learning Application on Descriptive Text for Junior High School Students - Sofiani; Afrianto; Jismulatif (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
The following aims guided the conduct of this study: Developing Smartphone-based Learning application based on animal descriptions. Understanding the viability of a smartphone-based learning application focused on descriptive writings about animals. In this study, the researcher used the Research and Development (R&D) approach with the ADDIE development stages (analysis, design, development, implementation, and evaluation), especially the analysis, design, development, implementation, and evaluation phases, but research was only conducted until the development stage. Material and media professionals carried out media validation. The Articulate Storyline 3 application was used to develop Android application-based learning media based on descriptive text about animals. The material expert's validation results obtained an average rating of 4.77 in the area of